PENGARUH STRATEGI PEMBELAJARAN AKTIF TIPE THE LEARNING CELL DISERTAI HANDOUT TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS IX SMPN 1 KUBUNG KABUPATEN SOLOK - Novriani, Riva; Zulfaneti, Zulfaneti; Yunita, Alfi (STKIP PGRI Sumbar, 2013)
The research was background by an understanding of mathematical concepts students are still low and the students did not dare to ask the teacher. The purpose of this research was to determine the effect of active learning type The Learning Cell with handout about understanding of mathematical concepts students better than understanding of mathematical concepts students with conventional learning. Kind of this research is experiment with plan random on subyek. The population is IX SMPN 1 Kubung Kabupaten Solok and sample it IX3 as experiment class and IX5 as control class. This research use instrument is essay, that test about understanding of mathematical concepts students consist of 6 itemÂ with reliability testÂ 0,8238. By virtue of data analysis get average of result learning of student experiment class better than control class. Hypothesis use test t-one way with software MINITAB, result P-value 0,022 less than Â is 0,05 so hypothesis acceptable. So the conclusion is learning with active learning type The Learning Cell with handout better than conventional learning at IX SMPN 1 Kubung Kabupaten Solok.